DEVELOPMENT OF AGGLUTININS AND PROTECTIVE ANTIBODIES IN RABBITS, AFTER INHALATION OF TYPE II PNEUMOCOCCI - Stillman, Ernest G. (The Rockefeller University Press, 1930)
1. Following repeated inhalations of the degenerated non-virulent "R" forms of Type II pneumococcus, no type specific antibodies can be demonstrated in the serum of rabbits. 2. Following repeated inhalations of slightly virulent Type II (SAv) pneumococci, only protective antibodies can be demonstrated in the serum of rabbits. 3. Following repeated inhalations of virulent Type II (Sv) pneumococci, agglutinins and protective antibodies can be demonstrated in the serum of rabbits. 4. Following repeated exposures of rabbits to inhalation of pneumococci, the type specific response, evidenced by type specific protective antibodies and agglutinins, varies in direct proportion to the virulence of the culture used.